Bio-functionalization of lanthanide phosphate nanoparticles / Abbas Abdulameer Salman - Salman, Abbas Abdulameer (2014)
A series of new surface modification reagents were synthesized and applied on LaPO4:Ce,Tb nanoparticles surfaces by postsynthetic and in-situ nanoparticle modification. The compounds comprise of an oligo-ethlyne glycol backbone that is connecting an organic phosphonate function (ester, acid or acid salt) and a reactive functional group (azide or alkyne), suitable for coupling with complimentary functionalized carbohydrates by cycloaddition in click chemistry fashion. The objective of this chemical functionalization of a nanoparticle is to attach a biological receptor that enables subsequent direction of the particle in the human body for related life science application, e.g. as radio-contrast reagent for the specific recognition of cancer cells. The bio-labeling process involves two stages; in the initial stage the phosphonate binds covalently to the surface, thus chemically attaching the reactive functional group to the particle. Subsequent coupling with receptor under mild click-chemistry conditions enables the binding of the latter to the particle. Monitoring of chemical changes at the particle surface was based on IR-spectroscopy. The reaction progress was monitored by tracking azide and carbonyl vibrations. The particle loading with the organic ligand was confirmed by TGA. Furthermore, the size, shape and morphology of the LaPO4:Ce,Tb nanocrystals were examined by XRD, SAXS and transmission electron microscopy. The experimental results confirm a previously reported narrow monodisperse distribution of ellipsoidal nanoparticle with 5-7 nm diameter. They also indicate no effect of neither surface modification nor subsequent click coupling on the particle morphology.